Pengaruh Lingkungan Keluarga dan Lingkungan Sekolah terhadap Motivasi Belajar Siswa di Desa Simpang Koje - Misdayani Jambak (Jurnal Pendidikan dan Humaniora Rumbio, 2026)
Learning motivation is one of the essential components that determines students’ academic performance and overall learning outcomes. In rural areas such as Simpang Koje Village, external factors, particularly family and school environments, significantly influence students’ willingness and enthusiasm to learn. This study aims to examine the impact of both environments on students’ learning motivation in Simpang Koje Village using a descriptive qualitative approach. Data were collected through observations, informal interviews with teachers, students, and parents, and relevant literature review. The findings reveal that parental involvement, availability of learning facilities at home, and family socioeconomic conditions play major roles in shaping students' motivation. Meanwhile, the role of teachers, the quality of school facilities, learning atmosphere, and peer interaction also contribute significantly to students’ motivation. Major challenges include limited parental supervision due to work demands and inadequate modern educational resources. This study highlights the importance of strong collaboration between families and schools to create a supportive learning environment that fosters higher academic motivation and achievement among rural students.